Agribusiness diversification into digitalisation: a marketing risk or a strategy for survival? - Chaham, Hamza R.; Bosire, Brian; Ricau, Pierre (Technical Centre for Agricultural and Rural Cooperation, 2019)
African agribusiness start-ups are developing business models that deliver multiple tech-driven solutions to address the varying needs of smallholder farmers. Whilst this can be key for the financial sustainability of new businesses, according to agri-ent